Ensemble Combo Band For The Visually Impaired Person At SLB Negeri 1 Dauh Puri Klod, Denpasar Barat - Agustinus Sani Aryanto; I Komang Darmayudha; Maria Regina Ayu Tri Wina Yuhari (JSM (Jurnal Seni Musik), 2022)
SLB Negeri 1 Denpasar is one of the knowledge forums for children with special needs, one of them is visually impaired, for them to be able to study, and develop their talents in art, especially music. This research focuses on the process and role provided through the ensemble music combo band for children with visual impairments.